The Role of Innovations in Modern Economy - Djalilova Nigora Mavlonovna (Research Parks Publishers, 2022)
In this article, innovation is becoming one of the most characteristic features of economic development and is analyzed as a factor accelerating the development of the market. Also we have given our suggestions and recommendations, today’s world through the widespread use of innovation.